2015
DOI: 10.1186/s12874-015-0069-z
|View full text |Cite
|
Sign up to set email alerts
|

Methodology and reporting quality of reporting guidelines: systematic review

Abstract: BackgroundWith increasing attention put on the methodology of reporting guidelines, Moher et al. conducted a review of reporting guidelines up to December 2009. Information gaps appeared on many aspects. Therefore, in 2010, the Guidance for Developers of Health Research Reporting Guidelines was developed. With more than four years passed and a considerable investment was put into reporting guideline development, a large number of new, updated, and expanded reporting guidelines have become available since Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
(42 reference statements)
0
35
0
Order By: Relevance
“…18 Previous working groups aiming to achieve standardised endpoints within healthcare 21,22 have seldom adopted a formal consensus gathering process, such as the one used in this study. 23 A review of healthcare guideline development by Wang and colleagues 24 found that >30% did not report how a consensus was gained and the remaining did so poorly. It is vital to ensure that high standards and consistency regarding methodology are implemented.…”
Section: Discussionmentioning
confidence: 99%
“…18 Previous working groups aiming to achieve standardised endpoints within healthcare 21,22 have seldom adopted a formal consensus gathering process, such as the one used in this study. 23 A review of healthcare guideline development by Wang and colleagues 24 found that >30% did not report how a consensus was gained and the remaining did so poorly. It is vital to ensure that high standards and consistency regarding methodology are implemented.…”
Section: Discussionmentioning
confidence: 99%
“…There is general consensus that reporting guidelines are important for improving the quality of medical research (Wang et al . 2015). The CAse REport (CARE) guidelines (Gagnier et al 2013) were developed through a consensus process, aimed at improving the reporting of information in case reports within the field of Medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, insufficient reporting impedes the applicability and misrepresents results used by patients and practitioners 1. To improve the quality of research, experts have developed reporting guidelines 2. Reporting guidelines are important tools for improving the quality of medical research 2.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the quality of research, experts have developed reporting guidelines 2. Reporting guidelines are important tools for improving the quality of medical research 2. The number of reporting guidelines in the Enhancing the QUAlity and Transparency Of health Research (EQUATOR) Network’s Library has increased.…”
Section: Introductionmentioning
confidence: 99%